Consumer cosmopolitanism in international marketing research: a systematic review and future research agenda - Makrides, Anna; Kvasova, Olga; Thrassou, Alkis; Hadjielias, Elias; Ferraris, Alberto (My University, 2021)
Purpose: The purpose of this study is to systematically collate and scrutinize the state of the art on consumer cosmopolitanism (CCOS) from an international marketing perspective and to provide a foundation for future research on the subject matter to proliferate and prosper. Design/methodology/approach: A systematic review of the extant literature was conducted focusing on peer-reviewed journal articles published in major marketing, international business and management journals. Findings: A systematic analysis of 44 journal articles shows that CCOS research is a rapidly growing research stream in the international marketing field. However, at the same time, the results reveal a lack of coherent and consistent conceptual underpinning, conflicting empirical findings regarding the profile and behavior of cosmopolitan consumers, persisting knowledge gaps, as well as methodological and contextual weaknesses. Originality/value: This paper is the first to consolidate the pertinent literature on CCOS. In doing so, it provides a roadmap for future research with reference to theory, context and methodology based on the research inconsistencies and knowledge gaps identified, contributing toward the development of this research area.
Keywords: Consumer cosmopolitanism; International marketing; Consumer behavior; International market segmentation; Systematic review